Transactions on Computational Science XX Special Issue on Voronoi Diagrams and Their Applications - Gavrilova, Marina L.; Tan, C. J. Kenneth; Kalantari, Bahman; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This, the 20th issue of the Transactions on Computational Science journal, edited by Bahman Kalantari, is devoted to the topic of Voronoi Diagrams and their applications. The 10 full papers included in the volume are revised and extended versions of a selection of papers presented at the International Symposium on Voronoi Diagrams 2012, held in Rutgers, NJ, USA, in June 2012. They provide an in-depth overview of current research on topological data structures and a comprehensive evaluation of their applications in the fields of cartography, physics, material modeling, chemistry, GIS, motion planning and computer graphics.
The State of the Art of Voronoi Diagram Research -- DT-RANSAC: A Delaunay Triangulation Based Scheme for Improved RANSAC Feature Matching -- On the Construction of Generalized Voronoi Inverse of a Rectangular Tessellation -- Localizing the Delaunay Triangulation and Its Parallel Implementation -- Decomposition of a Protein Solution into Voronoi Shells and Delaunay Layers: Calculation of the Volumetric Properties -- Proximity and Motion Planning on l1-Rigid Planar Periodic Graphs -- Tunnels and Voids in Molecules via Voronoi Diagrams and Beta-Complexes -- On Properties of Forbidden Zones of Polygons and Polytopes -- Voronoi-Based Medial Axis Approximation from Samples: Issues and Solutions -- Globally Rigid Ball-Polyhedra in Euclidean 3-Space -- On Voronoi Diagrams in the Planar Line Space and Their Generalizations.
Keywords: Computer science; Artificial intelligence; Computer graphics; Computer vision; Computer Science; Computer Graphics; Image Processing and Computer Vision; Artificial Intelligence (incl. Robotics).